ORGANIZE SELF-DEPENDENT COGNITIVE ACTIVITY OF PUPILS ON PHYSICS USING INFORMATION TECHNOLOGIES (Journal of Information Technologies in Education (ITE), 2012)
This article discusses the possibility of training teachers of physics to development of students' cognitive independence means of information technology.
Keywords: cognitive autonomy; information technology in education; training future teachers of physics